2014
DOI: 10.1021/ma500612x
|View full text |Cite
|
Sign up to set email alerts
|

Design of Novel Photoinitiators for Radical and Cationic Photopolymerizations under Near UV and Visible LEDs (385, 395, and 405 nm).

Abstract: Three novel photoinitiators, namely (2,2′-bithiophen-5-yl)(4-(N,N′dimethylaminophenyl)ketone, 5,10-dimethoxybenzo[j]fluoranthene and 6,6′-(((1E,1′E)-(2,5-bis(octyloxy)-1,4-phenylene)bis(ethene-2,1-diyl))bis(4,1-phenylene))bis(1,3,5-triazine-2,4-diamine) applicable to different near UV or visible LEDs (385 nm, 395 nm, 405 nm or cold white LED) have been developed. When incorporated into multicomponent photoinitiating systems PISs (in the presence of iodonium salt (and optionally N-vinyl carbazole) or amine/alky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 40 publications
2
69
1
Order By: Relevance
“…(a,b)]. As reported in previous related studies, reactive initiating species are Ph • and Ph‐NVK • for FRP, cations (Ph‐NVK + ) and possibly the oxidized form of the photocatalyst for CP in irradiated FeCs/Iod or FeCs/Iod/NVK systems according to reactions 1–6 (Scheme ). In FeCs/EDB/R′‐Cl, aminoalkyl (EDB (H) • ), and R′ • radicals are likely formed as indicated in reactions 7–11 (Scheme ) to initiate the FRP (as also described in other systems).…”
Section: Resultsmentioning
confidence: 71%
“…(a,b)]. As reported in previous related studies, reactive initiating species are Ph • and Ph‐NVK • for FRP, cations (Ph‐NVK + ) and possibly the oxidized form of the photocatalyst for CP in irradiated FeCs/Iod or FeCs/Iod/NVK systems according to reactions 1–6 (Scheme ). In FeCs/EDB/R′‐Cl, aminoalkyl (EDB (H) • ), and R′ • radicals are likely formed as indicated in reactions 7–11 (Scheme ) to initiate the FRP (as also described in other systems).…”
Section: Resultsmentioning
confidence: 71%
“…6(a)]. 8,39,50 When mixing with Iod, the key step is the photoinduced electron transfer (PET) process between the PI/Iod photoredox pair. The PET from the excited dye ( 1 PI) to iodonium (Ph 2 I 1 ) leads to the dye radical cation (PI •1 ) and neutral radical (Ph • ), as shown in the ESR-ST curve in Figure 6(b).…”
Section: Excited States Reactions Of Pis Themselves and With Pis And mentioning
confidence: 99%
“…The FRP should work according to the reactions (r 1 and r 4 ) by comparing with other photoinitiating systems. 41,50,54,55 …”
mentioning
confidence: 99%
“…General strategies to conduct cationic polymerization at the visible range involve the oxidation of free radicals by onium salts (also called free‐radical promoted cationic polymerization), the formation of charge transfer complexes, and electron transfer reaction within the exciplexes of polynuclear aromatic compounds and onium salts. Lalevee et al have shown that various dyes, silanes, and polythiophenes can efficiently induce a reduction in onium salts, even at a visible range.…”
Section: Introductionmentioning
confidence: 99%